Application of lignin from oil palm empty fruit bunch (EFB) in surfactant formulation - Wan Jaafar, Wan Mohammad Kamal (David Pub., 2010)

(untitled)
The use of surfactant in enhanced oil recovery (EOR) can help to increase oil production by lowering the interfacial tension at oil-water interfaces. However, the costs of surfactants derived from petroleum-based source are very expensive. In this study, lignin was extracted from black liquor obtained by pulping oil palm empty fruit bunch (EFB) with NaOH. The properties of extracted lignin were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet (UV) and Nuclear Magnetic Resonance (13C-NMR). The extracted lignin was used with amine and Sodium Dodecyl Sulfate (SDS) to form surfactant formulation for application in surfactant flooding. The stability and interfacial tension (IFT) of the formulation formed were determined. Based on the FTIR, UV and 13C-NMR results, there were no significant differences between extracted lignin and standard lignin. The results show that this formulation is stable and it can produce lower IFT compared to SDS and amine. This shows that lignin based surfactants have a good potential to be used in surfactant flooding.